2015
DOI: 10.17222/mit.2014.039
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis and modeling of the buckling of a loaded honeycomb sandwich composite

Abstract: Sandwich panels have the best stiffness-to-lightness ratio, which is what makes them very useful in industrial applications. This paper is focused on a study of the buckling capacities of the core components under uniaxial compression. The critical buckling loads for various core densities and materials of honeycomb panels were experimentally and numerically investigated. The specimens under lateral loading showed three zones: zone 1 is the initial elastic state, followed by the plateau region in zone 2, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…At (2015), A. Bentouhami et. al., [2], investigated the effect of buckling behavior of core component under compression load. Where the investigation included the estimation of the buckling load for core by two techniques, the first, was the experimental technique and the second was the numerical investigation, and then, a comparison of the results together was done.…”
Section: Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…At (2015), A. Bentouhami et. al., [2], investigated the effect of buckling behavior of core component under compression load. Where the investigation included the estimation of the buckling load for core by two techniques, the first, was the experimental technique and the second was the numerical investigation, and then, a comparison of the results together was done.…”
Section: Usedmentioning
confidence: 99%
“…Where, the comparison of the analytical and numerical results showed a good agreement of results with a maximum error about (2.24%). Finally, the results showed that the buckling load is modified by increasing the honeycomb core size. There, the upper and lower sheet plate could be used as metal or non-metal materials, [2]. Also, the honeycomb sandwich structure can be made from various materials types as metal, ceramic, composite materials etc.…”
mentioning
confidence: 99%
“…It was found that the yield stress by the finite element analysis in ANSYS/LS-DYNA on the structure is more than that of the experimental test done on the structure by 6.7% . The structural nonlinear was not considered due to which error occurred [1]. Surya Satish Adapa, et al the deflection variation in honeycomb sandwich structure is carried out.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is noted that many innovative designs and optimizations of PCs lead to wider BGs in lower frequency ranges [16,17], while for sandwich plates, the frequency band gaps are not wide and low enough [1820] or the band gaps are lower while core materials are quite expensive [21]. It should also be pointed out that for periodic sandwich plates the vast majority of experiments concern more about strength, stiffness or buckling than vibration isolation [2227]. In the present paper, a kind of PC sandwich plate with a periodic hollow tube core is investigated numerically and experimentally.…”
Section: Introductionmentioning
confidence: 98%